2020
DOI: 10.1111/pan.13787
|View full text |Cite
|
Sign up to set email alerts
|

Airway management and perioperative adverse events in children with mucopolysaccharidoses and mucolipidoses: A retrospective cohort study

Abstract: Background Children suffering from mucopolysaccharidoses (subtypes I, II, III, IV, VI, and VII) or mucolipidoses often require anesthesia, but are at high risk for perioperative adverse events. However, the impact of the disease subtype and the standard of care for airway management are still unclear. Aims This study aimed to assess independent risk factors for perioperative adverse events in individuals with mucopolysaccharidoses/mucolipidoses and to analyze the interaction with the primary airway technique i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 31 publications
(90 reference statements)
3
26
0
2
Order By: Relevance
“…This patient was then successfully intubated using a GlideScope® videolaryngoscope. Again, our findings support the conclusion of Dohrmann 9 that a specific type of indirect intubation technique cannot be recommended in all children with MPS/ML and thus anesthetists caring for these complex children must be skilled in a range of advanced pediatric airway management techniques.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…This patient was then successfully intubated using a GlideScope® videolaryngoscope. Again, our findings support the conclusion of Dohrmann 9 that a specific type of indirect intubation technique cannot be recommended in all children with MPS/ML and thus anesthetists caring for these complex children must be skilled in a range of advanced pediatric airway management techniques.…”
Section: Discussionsupporting
confidence: 84%
“…Thus, a fiber‐optic or videolaryngoscope technique are often utilized first‐line for potentially difficult airways. Our practice is supported by the findings of a recent cohort study of airway management and perioperative adverse events in children with MPS and ML where Dohrmann et al found that direct laryngoscopy was associated with a much higher probability for airway management problems and respiratory adverse events compared to indirect techniques 9 …”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…A high rate of failed direct laryngoscopy and respiratory events prove an especially difficult airway and call for advanced airway management in these patients [5,10]. We recently published that the anaesthetic risk is higher in patients with MPS types I or II than with MPSIII and suggested using indirect intubation techniques as the first-line airway approach in individuals with MPS [11].…”
Section: Introductionmentioning
confidence: 99%
“…Мукополисахаридоз (МПС) -орфанное заболевание, относящееся к группе лизосомных болезней накопления. Известно [1][2][3][4][5][6]. Накопление гликозаминогликанов (ГАГ) вызывает задержку физического развития, умственную отста-На фоне бурно прогрессирующей кифотической деформации наблюдалось нарастание неврологического дефицита.…”
Section: обоснованиеunclassified